2007
DOI: 10.1037/0096-1523.33.6.1377
|View full text |Cite
|
Sign up to set email alerts
|

Developmental dissociations of preparation over time: Deconstructing the variable foreperiod phenomena.

Abstract: In a variable foreperiod (FP) paradigm, reaction times (RTs) decrease as a function of FP on trial n (FP effect) but increase with FP on trial n - 1 (sequential effects). These phenomena have traditionally been ascribed to different strategic preparation processes. According to an alternative explanation, common conditioning laws underlie both effects. The present study aims to disentangle these opposite views using a developmental perspective. In Experiment 1A, 4- to 11-year-old children and a control group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
145
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(162 citation statements)
references
References 44 publications
17
145
0
Order By: Relevance
“…Consistent with our findings that implicit forms of timing mature early and are age invariant, Vallesi and Shallice (2007) and Mento and Tarantino (2015) also found that the strength of the variable foreperiod effect was very similar in adults and children older than 6 years. Johnson and colleagues (2015), on the other hand, found that the variable foreperiod effect was actually even stronger in children than in adults.…”
Section: Tablesupporting
confidence: 91%
“…Consistent with our findings that implicit forms of timing mature early and are age invariant, Vallesi and Shallice (2007) and Mento and Tarantino (2015) also found that the strength of the variable foreperiod effect was very similar in adults and children older than 6 years. Johnson and colleagues (2015), on the other hand, found that the variable foreperiod effect was actually even stronger in children than in adults.…”
Section: Tablesupporting
confidence: 91%
“…However, this finding is not inconsistent with the predictions of MTP, because recent memory traces-especially the most recent one-are assumed to carry more weight than older traces in their contribution to preparation on the current trial (see also Los et al, 2014). This mechanism allows MTP to account for short-term effects lasting a few trials (i.e., asymmetric sequential effects), which have been shown to make a robust contribution to RT (e.g., Los, 2010;Los & Van den Heuvel, 2001;Steinborn & Langner, 2012;Vallesi & Shallice, 2007;Woodrow, 1914;Zahn et al, 1963). These sequential effects also contribute to the difference in RT-foreperiod functions between the exponential and antiexponential distributions (i.e., there are more primed short-short transitions in the exponential than antiexponential distribution; see Los & Agter, 2005, for a detailed discussion).…”
Section: Discussionmentioning
confidence: 61%
“…The observed transfer effect is hard to reconcile with models of temporal preparation based on the hazard function (e.g., Coull et al, 2011;Cui et al, 2009;Janssen & Shadlen, 2005;Vallesi & Shallice, 2007). The hazard function is derived from the current distribution of foreperiods without regard to their history.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations